Limited HLA sequence variation outside of antigen recognition domain exons of 360 10 of 10 matched unrelated hematopoietic stem cell transplant donor‐recipient pairs. (15th December 2016) - Hou, L.; Vierra‐Green, C.; Lazaro, A.; Brady, C.; Haagenson, M.; Spellman, S.; Hurley, C. K.
Abstract: Traditional DNA‐based typing focuses primarily on interrogating the exons of human leukocyte antigen (HLA) genes that form the antigen recognition domain (ARD). The relevance of mismatching donor and recipient for HLA variation outside the ARD on hematopoietic stem cell transplantation (HSCT) outcomes is unknown. This study was designed to evaluate the frequency of variation outside the ARD in 10 of 10 (HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1) matched unrelated donor transplant pairs ( n = 360). Next‐generation DNA sequencing was used to characterize both HLA exons and introns for HLA‐A, ‐B, ‐C alleles; exons 2, 3 and the intervening intron for HLA‐DRB1 and exons only for HLA‐DQA1 and ‐DQB1. Over 97% of alleles at each locus were matched for their nucleotide sequence outside of the ARD exons. Of the 4320 allele comparisons overall, only 17 allele pairs were mismatched for non‐ARD exons, 41 for noncoding regions and 9 for ARD exons. The observed variation between donor and recipient usually involved a single nucleotide difference (88% of mismatches); 88% of the non‐ARD exon variants impacted the amino acid sequence. The impact of amino acid sequence variation caused by substitutions in exons outside ARD regions in D–R pairs will be difficult to assess in HSCT outcome studies because these mismatches do not occur very frequently.